2011
DOI: 10.1007/s11065-011-9168-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Alcohol Exposure on Behavior: Rodent and Primate Studies

Abstract: The use of alcohol by women during pregnancy is a continuing problem. In this review the behavioral effects of prenatal alcohol from animal models are described and related to studies of children and adults with FASD. Studies with monkeys and rodents show that prenatal alcohol exposure adversely affects neonatal orienting, attention and motor maturity, as well as activity level, executive function, response inhibition, and sensory processing later in life. The primate moderate dose behavioral findings fill an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 154 publications
(198 reference statements)
4
105
0
Order By: Relevance
“…Although many disorders of genetic and/or environmental origin are associated with developmental delays in cognitive function (Cornish et al 2004;Sagvolden et al 2005;Riley et al 2011), most current animal models typically do not assess cognitive function until adulthood or perhaps at one or two isolated developmental stages. For instance, fetal alcohol exposure is consistently found to produce widespread effects on learning and memory in rodents that are present during adolescence and adulthood (Berman and Hannigan 2000;Schneider et al 2011), but relatively little is known regarding the developmental onset of these effects in younger animals (e.g., Blanchard et al 1987;Wigal et al 1988;Kirstein et al 1997). Our finding that the ability to form context-shock associations is delayed by up to 2 d in fetal alcohol-exposed mice demonstrates that a detailed ontogenetic timeline of contextual fear memory can be used as a template to compare normal vs. abnormal cognitive development.…”
Section: Learning and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Although many disorders of genetic and/or environmental origin are associated with developmental delays in cognitive function (Cornish et al 2004;Sagvolden et al 2005;Riley et al 2011), most current animal models typically do not assess cognitive function until adulthood or perhaps at one or two isolated developmental stages. For instance, fetal alcohol exposure is consistently found to produce widespread effects on learning and memory in rodents that are present during adolescence and adulthood (Berman and Hannigan 2000;Schneider et al 2011), but relatively little is known regarding the developmental onset of these effects in younger animals (e.g., Blanchard et al 1987;Wigal et al 1988;Kirstein et al 1997). Our finding that the ability to form context-shock associations is delayed by up to 2 d in fetal alcohol-exposed mice demonstrates that a detailed ontogenetic timeline of contextual fear memory can be used as a template to compare normal vs. abnormal cognitive development.…”
Section: Learning and Memorymentioning
confidence: 99%
“…Pinpointing the precise age when animals begin to form memories of aversive events can be valuable for understanding the onset of anxiety and mood disorders stemming from maladaptive early life experience (Pine 2009;Bale et al 2010;Marco et al 2011) and for detecting early cognitive impairment in models of autism, attention deficit/hyperactivity disorder, and fetal alcohol syndrome (Schneider et al 2011;Kaffman and Krystal 2012). During infancy and adolescence, the progressive growth and refinement of neural circuitry supporting sensation and perception (Bourne 2010;Froemke and Jones 2011), cognition (Benes et al 2000;Dumas 2005), and emotion (Braun 2011) gradually enables young rodents to begin learning about their surroundings.…”
mentioning
confidence: 99%
“…
INTRODUCTIONStudies with rodents show that prenatal exposure to some neurotoxicants adversely affects neonatal orientation, attention and motor maturity, as well as activity level, executive function, response inhibition and sensory processing later in life (Schneider et al, 2011). Although there have been a vast number of animal toxicological studies carried out on pregnant animals including embryos/fetuses and mature animals, there is a paucity of reports on animal toxicology studies utilizing newborn animals a few days after birth.
…”
mentioning
confidence: 99%
“…Animal models using higher-order primates (rhesus monkeys) mirror those conducted with rodents and have demonstrated that, under conditions of prenatal stress and alcohol exposure, outcomes include lower birth weights, increased stereotypical behavior, reduced attention span, decreased exploration and play behavior, and increased activity levels early in life [26]. Importantly, prenatally stressed adolescent monkeys with PAE exhibit an increase in alcohol preference over time, suggesting a vulnerability to SUDs similar to that found in humans.…”
Section: Animal Models Of Mental Health Problemsmentioning
confidence: 99%